2009
DOI: 10.1371/journal.pone.0004959
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Lobe Cortical Electrical Stimulation during the Encoding and Retrieval Phase Reduces False Memories

Abstract: A recent study found that false memories were reduced by 36% when low frequency repetitive transcranial magnetic stimulation (rTMS) was applied to the left anterior temporal lobe after the encoding (study) phase. Here we were interested in the consequences on a false memory task of brain stimulation throughout the encoding and retrieval task phases. We used transcranial direct current stimulation (tDCS) because it has been shown to be a useful tool to enhance cognition. Specifically, we examined whether tDCS c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
73
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 30 publications
8
73
0
3
Order By: Relevance
“…In particular, immediate free recalls of the standard list on the 5th and on the 6th trials (the latter after presentation of the IL) were significantly improved by tSOS compared with sham (F 1,11 Ͼ 6.22, P Ͻ 0.03). In light of recent findings (20,21) of effects of transcranial stimulation on the rate of false memories, we analyzed aside from total errors also the number of falsely recalled words (i.e., words not in the standard list), preservation type (repetitions) errors, and accuracy (ratio of total correct words by total cited words), but did not find any differences between the sham and tSOS conditions (each P Ͼ 0.1) ( Table 2; Table S2). Recognition performance on the number list learning task was not sensitive to tSOS (F 1,11 Ͻ 0.74, P Ͼ 0.41) ( Table 2), supporting other studies on differential mechanisms underlying free-recall and recognition (22)(23)(24).…”
Section: Improved Encoding Of Verbal Memory By Tsos Applied During Lementioning
confidence: 78%
See 1 more Smart Citation
“…In particular, immediate free recalls of the standard list on the 5th and on the 6th trials (the latter after presentation of the IL) were significantly improved by tSOS compared with sham (F 1,11 Ͼ 6.22, P Ͻ 0.03). In light of recent findings (20,21) of effects of transcranial stimulation on the rate of false memories, we analyzed aside from total errors also the number of falsely recalled words (i.e., words not in the standard list), preservation type (repetitions) errors, and accuracy (ratio of total correct words by total cited words), but did not find any differences between the sham and tSOS conditions (each P Ͼ 0.1) ( Table 2; Table S2). Recognition performance on the number list learning task was not sensitive to tSOS (F 1,11 Ͻ 0.74, P Ͼ 0.41) ( Table 2), supporting other studies on differential mechanisms underlying free-recall and recognition (22)(23)(24).…”
Section: Improved Encoding Of Verbal Memory By Tsos Applied During Lementioning
confidence: 78%
“…The application of tSOS during a wake retention interval (i) enhanced frontal EEG slow oscillation activity, but was otherwise associated with distinctly different effects than those observed previously after tSOS during sleep (18); (ii) tSOS during quiet and attentive wakefulness enhanced global activity in the theta (4-8 Hz) frequency band [beta activity (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) was additionally enhanced during quiet wakefulness]; (iii) retention of declarative memories during the wake retention interval was not improved; (iv) instead, tSOS during the process of encoding improved learning performance as assessed by immediate recall of words learned in the presence of stimulation. Our findings indicate that the effects of tSOS on memory function critically depend on the functional brain state (19,25).…”
Section: Discussionmentioning
confidence: 90%
“…Recent studies showed that working memory could be improved by anodal (Fregni et al, 2005;Andrews et al, 2011) or impaired by cathodal stimulation of the DLPFC (Elmer et al, 2009). Boggio et al (2009) demonstrated that recognition memory was subject to modulation as well: anodal tDCS of the anterior temporal cortex throughout the encoding and retrieval phases effectively decreased the rate of false positives in a recognition memory task, while keeping the rate of veridical memories unchanged. The present study demonstrates that tDCS also modulates orbitofrontal reality filtering.…”
Section: Discussionmentioning
confidence: 99%
“…Previous neuroimaging and patient studies have provided robust evidence that a core network of regions in the medial and lateral temporal lobe, as well as frontal and parietal regions (8)(9)(10)(11)(12)(13)(14)(15)(16), is involved when encoding or retrieving semantic false memories. However, a mechanistic understanding of how these regions generate false memories is lacking.…”
mentioning
confidence: 99%